(untitled) (Research, Society and Development, 2023)
Objective: To prepare standard operating protocols (SOPs) for the preparation of instruments used in nail cutting. Methods: Descriptive research, with elaboration of educational videos about preparation and sterilization of instruments for non-medical liability beauty institutes (NMSI). Two (SOPs) were elaborated: 1- Use of Personal Protective Equipment (PPE) for manipulation of cutting instruments. 2- Processing of instruments for cuticle removal (pliers and retractors). Results: The 02 SOP’s elaborated were in video format, with paramentation and unparamentation of the PPE’S and preparation of the cuticle Instruments, containing the flow of cleaning with neutral soap, packaging with surgical grade paper, sterilization by steam autoclave. Conclusion: The SOP’s elaborated when well used, have the intention to offer subsidies for the activities of nail cutting with safety, minimizing the risks and possible damages to the health of the professionals and the customers, about the exposure to pathogens, such as hepatitis C (HCV), hepatitis B (HBV), Human Immunodeficiency Virus (HIV) linked by a possible contamination of the instruments with blood, finally the training is fundamental for the consolidation of the correct use of the SOP and the achievement of biosecurity in beauty salons.